Study of the Quantum Dot and Theoretical Model of Hamiltonian of An Electron Interaction with Longitudinal Optical Phonons (International Journal of Scientific Research in Science and Technology, 2025)
In this present paper, we presented about the study of the quantum dot and present a theoretical model of Hamiltonian of an electron interaction with longitudinal optical phonons.